2007
DOI: 10.1002/app.26096
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, nonisothermal crystallization behavior, and kinetics of poly(phenylene sulfide)/polycarbonate blend

Abstract: The morphology and nonisothermal crystallization behavior of blends made of poly(phenylene sulfide) (PPS), with a amorphous polycarbonate (PC) were studied. The blend is found to be partially miscible by the dynamic mechanical thermal analysis (DMTA) and melt rheological measurements. The nonisothermal crystallization behavior of blend was studied by differential scanning calorimetry (DSC). The results show clearly that the crystallization temperatures of PPS component in the blend decrease with increasing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Poly(phenylene sulfide) (PPS) is one of the most important thermoplastic engineering polymers because of exhibiting excellent thermal stability, chemical resistance, and flame resistance. These literatures mainly focus on the crystallization morphology of PPS in quiescent condition [3][4][5][6][7][8][9][10][11][12] or in shear condition, [13][14][15] the PPS/other polymers or fillers composites, [16][17][18][19][20][21][22] the relation between molecular structure and crystallization behavior, 23,24 the crystallization kinetics, [25][26][27][28][29][30] and the influence of crystallinity on properties. 2 The transcendent properties of PPS greatly depend on its unique structure especially on its crystallizability.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(phenylene sulfide) (PPS) is one of the most important thermoplastic engineering polymers because of exhibiting excellent thermal stability, chemical resistance, and flame resistance. These literatures mainly focus on the crystallization morphology of PPS in quiescent condition [3][4][5][6][7][8][9][10][11][12] or in shear condition, [13][14][15] the PPS/other polymers or fillers composites, [16][17][18][19][20][21][22] the relation between molecular structure and crystallization behavior, 23,24 the crystallization kinetics, [25][26][27][28][29][30] and the influence of crystallinity on properties. 2 The transcendent properties of PPS greatly depend on its unique structure especially on its crystallizability.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization behavior of PPS in PPS composites with solid fillers10–22 and several other thermoplastic polymers23–40 has been studied extensively. The blending of fibrous fillers was found to result in enhanced rate of crystallization, particularly by armid fibers 10–14.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there have been a number of reports on the nonisothermal crystallization and melting behavior of PPS in its blends with other thermoplastics 23–27. For example, Zhang et al23 found that in PPS/poly (ether ether ketone) (PEEK) blend, the crystalline PEEK markedly accelerated the crystallization rate of PPS and changed the crystallization mechanisms of PPS from homogeneous to heterogeneous nucleation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods were developed to overcome those marginal properties. One approach is to blend PPS with other polymers to improve impact strength and high heat distortion temperature [3][4][5][6][7][8][9][10][11][12][13]. Another approach to increase the glass transition temperature and toughness is to manufacture the filled PPS composites.…”
Section: Introductionmentioning
confidence: 99%